Analisis Pentingnya Pasrtisipasi Masyarakat dalam Pembentukan Suatu Undang-Undang - Talita Sembiring; Kania Nova Ramadhani; Gadis Prasiska; Ruth Yessika Siahaan; Chairun Nisa; Ramsul Nababan; Maulana Ibrahim (Hakim, 2024)
Community participation is a stage where the community participates in the process of drafting laws and regulations. Therefore, the purpose of this research is to analyze the background of the need for communities to participate in the process of forming laws and regulations and the challenges faced by local communities when involved in the process of forming laws and regulations. This research uses a descriptive qualitative method with a literature study, which is a data collection technique by reviewing books, literature, memos, and various reports related to the problem to be solved, in order to develop productivity concepts that can be used as a foundation. The results of this study show that community participation is a stage that provides opportunities for the community to participate in the preparation of laws and regulations in accordance with the provisions of the law. Community participation is a mandatory legal norm. So that public participation becomes a mandatory process when drafting laws and regulations.